Inductive Insights into Preserving Euler Characteristics in Topological Transformations - Kunwar, Rajendra; Laxmi G. C (MASI Mandiri Edukasi, 2024)
Topological transformations involve altering the shape or structure of surfaces without changing their fundamental properties. One key property is the Euler characteristic, a topological invariant that remains constant under continuous deformations. This study employs an inductive approach to explore how various transformations can preserve the Euler characteristic, providing insights into the underlying principles. The study aims to deepen our understanding of the relationship between topological transformations, changes in the number of vertices, edges, and faces, and their impact on Euler's characteristics. The study investigates the transformation of various objects, such as spheres and polyhedra, within the Euclidean plane, deriving generalizations about preserving Euler's characteristics. Furthermore, the article explores the ideas of proving Euler's theorems related to topological transformations in the Euclidean plane through an inductive approach. It focuses on the conceptual development of topological transformations, utilizing various visual representations and providing specific arguments. The article enhances the understanding of the concepts and principles involved in topological transformations while preserving Euler's characteristics by employing visual aids and illustrations. The article emphasizes explicitly the inductive derivation of the application of Euler's theorem in determining the genus of surfaces. The inclusion of visual representations and specific arguments further enhances the understanding and conceptual development of these topics.